CHARLES BAUDELAIRE AND THE SPIRITUAL IN THE ARTS: A COMPARATIVE STUDY BETWEEN POETRY AND MODERN PAINTING - Goncalves, Aguinaldo Jose [UNESP]; Narvaes, Giuliarde de Abreu [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2017)
There is no way to traverse the poetic work of Charles Baudelaire without considering at any moment, and is expected not to be late, the persistence of poetic correspondences. In this work, through an intersemiotic analysis of language systems, we highlight structural correspondences between two sonnets of Les fleurs du mal and the plastic modernity of the works of Wassily Kandinsky and Jackson Pollock. A central and determining aspect to the comparative readings we will present, the theory of correspondences in Baudelaire's poetry becomes an inescapable subject for any comparative approach between his poetry and the plastic works of modernity.
Keywords: Baudelaire; intersemiotic; correspondence; arts; modernity